2018
DOI: 10.1038/s41426-018-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel triple-reassortant influenza viruses in pigs, Guangxi, China

Abstract: Considered a “mixing vessel” for influenza viruses, pigs can give rise to new influenza virus reassortants that can threaten humans. During our surveillance of pigs in Guangxi, China from 2013 to 2015, we isolated 11 H1N1 and three H3N2 influenza A viruses of swine origin (IAVs-S). Out of the 14, we detected ten novel triple-reassortant viruses, which contained surface genes (hemagglutinin and neuraminidase) from Eurasian avian-like (EA) H1N1 or seasonal human-like H3N2, matrix (M) genes from H1N1/2009 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Among the reassortant H1N1 viruses isolated in our study, G6-like and G14-like viruses were only sporadically detected in 2014, while G15-like reassortants were repeatedly isolated between 2014 and 2016 in Liaoning Province. Recent surveillance results from other provinces in China confirmed the multiple genomic characteristics of SIVs (19,20). Especially, G15-like viruses were continuously isolated, which suggested that these kinds of reassortant viruses have become established in the swine population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Among the reassortant H1N1 viruses isolated in our study, G6-like and G14-like viruses were only sporadically detected in 2014, while G15-like reassortants were repeatedly isolated between 2014 and 2016 in Liaoning Province. Recent surveillance results from other provinces in China confirmed the multiple genomic characteristics of SIVs (19,20). Especially, G15-like viruses were continuously isolated, which suggested that these kinds of reassortant viruses have become established in the swine population.…”
Section: Discussionmentioning
confidence: 90%
“…Pigs are considered a mixing vessel for the generation of such viruses, with genetic material originating from pigs, humans, and/or birds (12). Since 2009, genetic reassortment among the pandemic 2009/H1N1 virus, EA H1N1, and other swine H1N1, H1N2, and H3N2 viruses was detected repeatedly in pigs (13)(14)(15)(16)(17)(18)(19)(20). Notably, sporadic human infections of endemic and novel reassortant SIVs (21)(22)(23)(24)(25)(26)(27) and the seropositivity of at-risk populations, such as swine workers (28)(29)(30), underscore the importance of influenza surveillance in pigs.…”
mentioning
confidence: 99%
“…Symptomatic swine may exhibit mild or severe influenza like symptoms [59,202,252], including fever, coughing, sneezing, pneumonia, bronchitis, reduced appetite, diarrhea, nasal and/or ocular discharge, conjunctivitis, weakness, anorexia, prostration, weight loss, abortion in sows, and mortality in some cases [89,224,231,239,248,282,318]. Most studies where the swine were severely infected reported reduced appetite and weight loss [129,246,247,292].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a novel strain of avian-origin H4N1 virus was isolated from a Chinese swine in 2009 [80]. Several classical and avian-like H1N1, Eurasian avian-like H1N1, triple-reassortant H1N1, H1N2, H3N2 and A(H1N1)pdm09 viruses were reported in Chinese swine between 2009 and 2016 [81][82][83][84][85][86][87][88][89][90][91]. A triple-reassortant H1N1 virus having the internal genes of avian, human, and swine lineages of influenza viruses was reported from a two-month old piglet on a Guangdong based swine farm in January 2010 [92].…”
Section: Chinamentioning
confidence: 99%
“…Furthermore, there are some reports describing previous swine H1N1 reassortant viruses isolated from pigs in China (Bi et al, ; Cai et al, ; He et al, ; Sun et al, ; Xu et al, ). For example, some swine reassortant influenza viruses possessing H1N1 swine influenza virus genes (HA, NA and NS) and H1N1 human influenza virus genes (PB2, PB1, PA, NP and M) were found in pigs in Guangxi Province and Guangdong Province in China (Cai et al, ; He et al, ); several swine reassortant influenza viruses possessing swine influenza virus genes (HA, NA, M and NS) and H1N1 human influenza virus genes (PB2, PB1, PA and NP) were found in pigs in Tianjin city in China (Sun et al, ); one swine reassortant influenza virus possessing H1N2 avian influenza virus genes (PB2 and PA), H1N1 avian influenza virus genes (HA, NA and M), H1N2 human influenza virus gene (PB1), and H1N2 swine influenza virus genes (NP and NS) were found in pigs in Guangdong Province in China (Xu et al, ); one swine reassortant influenza virus possessing H9N2 avian influenza virus gene (PB1) and swine influenza virus genes (PB2, PA, HA, NP, NA, M and NS) was found in pigs in Shandong Province in China (Bi et al, ). Here, we report a novel reassortant H1N1 virus possessing swine influenza virus genes (PA, HA, NP, NA and NS) and human influenza virus genes (PB2, PB1 and M) and the prevalence of the swine influenza virus containing the HA gene of this novel reassortant virus in swine herds in Shandong Province, eastern China (Appendix Figure S1).…”
Section: Swine Serum Antibody Titres Against the Novel Reassortant Inmentioning
confidence: 99%